2021
DOI: 10.3390/jcm10061311
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Relationships and Associations between Cutaneous Manifestations and Inflammatory Bowel Disease: A Nationwide Population-Based Cohort Study

Abstract: The temporal relationships between inflammatory bowel disease (IBD)-associated cutaneous manifestations and IBD remain uncertain, with existing evidence mostly from separate cross-sectional studies. We sought to determine the risks of IBD-related dermatologic diseases before and after the diagnosis of IBD. We identified 2847 cases of IBD and 14,235 matched controls from the Taiwan National Health Insurance Research Database between 2003 and 2014. The risks of cutaneous manifestations before and after the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…One meta‐analysis study showed that erythema nodosum was found to be more common in CD than UC 33 . Following the diagnosis of IBD, EN was one of the earliest presentations of skin extraintestinal manifestations, with a median time of 3.55 years 32 . However, when EN was used as an exposure factor, there was no proof of a causal connection between IBD (its subtypes) and EN.…”
Section: Discussionmentioning
confidence: 99%
“…One meta‐analysis study showed that erythema nodosum was found to be more common in CD than UC 33 . Following the diagnosis of IBD, EN was one of the earliest presentations of skin extraintestinal manifestations, with a median time of 3.55 years 32 . However, when EN was used as an exposure factor, there was no proof of a causal connection between IBD (its subtypes) and EN.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable analysis revealed that the adjusted hazard ratios (aHRs) for incident CD and UC among patients with AE were 2.02 (95% CI, 1.118–3.663) and 1.51 (95% CI, 1.082–2.104), respectively. Furthermore, a nationwide population‐based cohort study of 2847 IBD cases and 14 235 matched controls from the Taiwan National Health Insurance Research Database (TNHIRD) showed that IBD is associated with AE (OR 1.61; 95% CI, 1.14–2.28) 18 . However, another nationwide TNHIRD (1997–2013) cohort study of 36 400 AE patients reported that AE is not independently associated with IBD development 19 …”
Section: Discussionmentioning
confidence: 99%
“…8 Numerous populationbased 9,10 and patient-based 11,12 studies and investigations [13][14][15] have suggested that the high frequency of clinical coexistence of AE and IBD indicates a strong correlation between them. Studies conducted in several regions, including East Asia, have pointed out that the risk of IBD increases with the development of AE; 7,9,[16][17][18] in contrast, Weng et al 19 reported that AE is not independently associated with IBD development.…”
Section: Introductionmentioning
confidence: 99%
“…Pyoderma gangrenosum (PG) is a rare, sterile, neutrophilic dermatosis of the skin. PG is a common cutaneous manifestation of inflammatory bowel disease (IBD), more frequently associated with ulcerative colitis than Crohn's disease (1)(2)(3). Approximately 30-40% of patients with PG have underlying IBD and a large proportion of them observe PG onset before their diagnosis of IBD is confirmed (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%